2010
DOI: 10.1021/ja1069882
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Peptide Self-Assembly: Transient α-Helices to Stable β-Sheets

Abstract: The pathologic self-assembly of proteins is associated with typically late-onset disorders such as Alzheimer's disease, Parkinson's disease, and type 2 diabetes. Important mechanistic details of the self-assembly are unknown, but there is increasing evidence supporting the role of transient α-helices in the early events. Islet amyloid polypeptide (IAPP) is a 37-residue polypeptide that self-assembles into aggregates that are toxic to the insulin-producing β cells. To elucidate early events in the self-assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
116
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(139 citation statements)
references
References 89 publications
17
116
0
Order By: Relevance
“…8). This sort of self-assembly based on transient a-helices has been demonstrated also for model peptides (48,63), islet amyloid polypeptide (64), and a-synuclein (44), and also in vivo for the assembly of silk into its cross-b structure (65).…”
Section: The Very N-terminus Of Ab Affects Its Fibrillization Kineticsmentioning
confidence: 73%
“…8). This sort of self-assembly based on transient a-helices has been demonstrated also for model peptides (48,63), islet amyloid polypeptide (64), and a-synuclein (44), and also in vivo for the assembly of silk into its cross-b structure (65).…”
Section: The Very N-terminus Of Ab Affects Its Fibrillization Kineticsmentioning
confidence: 73%
“…Similarly, it also is possible that domain swapping occurs prior to nucleation, resulting in the assembly of native-like but transient oligomeric aggregates. Note that various oligomeric assemblies of amyloidogenic proteins feature ␣-helical or native-like structures (66,67) that typically, but not always (68), are lost during fibril maturation.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially interesting in view of the NMR work of Lazo and coworkers, who reported that IAPP 11−25 structures with an induced kink in the central region were not aggregation prone. 51 Thus, stabilization of the kink in IAPP 1−37 by CLR01 provides a plausible structural explanation for the inhibition of aggregation by the molecular tweezer.…”
Section: Acs Chemical Biologymentioning
confidence: 96%